Who is healthy?: Aspects to consider when including healthy volunteers in Qst-based studies—a consensus statement by the Europain and Neuropain consortia - Gierthmühlen, Janne; Treede, Rolf-Detlef (Pain, 2015)
Clinical and human experimental pain studies often include so-called “healthy” controls in investigations of sensory abnormalities, using quantitative sensory testing (QST) as an outcome measure. However, the criteria for what is considered “healthy” vary among the different studies and between study centers and investigators, partly explaining the high variability of the results. Therefore, several aspects should be considered during inclusion of healthy volunteers in QST-based trials to have homogenous groups of healthy controls with less variability between human experimental studies, so that results are less likely to be false negative or false positive because of subject-related factors. The EUROPAIN and NEUROPAIN consortia aimed to define factors influencing the variability in selection of healthy subjects in QST-based studies before the start of both projects and to give recommendations how to minimize it based on the current literature and expertise of the participants. The present suggestions for inclusion criteria of healthy volunteers into QST-based trials describe a 2-level approach including standardized questionnaires enabling the collection of relevant information on sociodemographic data, medical history, current health status, coping strategies in dealing with pain, and the motivation of the volunteer to participate in the study. These suggestions are believed to help researchers interpret their results in comparison with others and improve the quality of clinical studies including healthy volunteers as controls or in human experimental pain studies. They aim to reduce any confounding factors. Furthermore, the acquired information will allow post hoc analyses of variance for different potential influencing factors.